2014
DOI: 10.1002/jmv.23937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sputum and nasopharyngeal swabs for detection of respiratory viruses

Abstract: Diagnostic tests for respiratory viral infections use traditionally either nasopharyngeal washes or swabs. Sputum is representative of the lower respiratory tract but is used rarely for viral testing. The aim of this study was to compare the detection rates of respiratory viruses from nasopharyngeal swabs and sputum using a multiplex real-time reverse transcription-polymerase chain reaction (RT-PCR). Adults who were admitted or presented to the clinics of Gil Medical Center with acute respiratory symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 16 publications
8
60
0
1
Order By: Relevance
“…Here, we investigated the diagnostic efficacy of nasopharyngeal aspirates versus pulmonary samples in a well-defined adult population of community-acquired severed LRTI and found that both diagnostic approaches gave similar diagnostic yield for respiratory viruses. This is discordant with several studies that have reported better performance for LRT samples for the diagnosis of viral infections in adults [10,11]. These studies where based on nasal, throat, or nasopharyngeal swabs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Here, we investigated the diagnostic efficacy of nasopharyngeal aspirates versus pulmonary samples in a well-defined adult population of community-acquired severed LRTI and found that both diagnostic approaches gave similar diagnostic yield for respiratory viruses. This is discordant with several studies that have reported better performance for LRT samples for the diagnosis of viral infections in adults [10,11]. These studies where based on nasal, throat, or nasopharyngeal swabs.…”
Section: Discussionsupporting
confidence: 78%
“…The superiority of lower over upper respiratory tract samples for the diagnosis of severe infuenza has been suggested by several authors [11,13]. We did not see such difference in our study, since 27 of 29 influenza virus infections were diagnosed in both specimens.…”
Section: Discussionsupporting
confidence: 43%
“…The use of sputum samples in our study may also explain our high IVE estimate. Identification of influenza from sputum samples may be more sensitive and specific than that from upper respiratory tract samples in diagnosing influenza pneumonia and may provide less biased IVE estimates [17,30,31]. Consistent findings in our sensitivity analyses also support the robustness of our IVE estimates.…”
Section: Influenza Vaccine Effectiveness In Older Adultssupporting
confidence: 80%
“…Real-time PCR Ct values are now considered by many to be a robust surrogate for quantified viral load and are increasingly reported in published studies of acute viral illness including those examining respiratory viruses [6,32] and also in the recent Ebola virus pandemic [33,34]. Furthermore, the use of protocolised sampling techniques, processing by dedicated research staff and the removal of inter-operator variability of results interpretation (as all samples were analysed by the same scientists in the same laboratory) gives reassurance as to the robustness of the Ct result in this study.…”
Section: Discussionmentioning
confidence: 99%